National mentality in children's literature - Akhmatov Abdulla Odil ugli; Mekhmonova Dilobar Vakhobjon kizi (Zien Journals, 2022)
This article addresses issues of national mentality of Uzbek children's literature. It also covers the development of children's literature and its national significance. The Uzbek views of children, philosophical scientific comments on the national values of children's literature are expressed
Keywords: children; children's literature; traditions; cultural richness